Effect of Taping on Feedforward Activity of the Non-dominant Leg Muscles in Elite Volleyball Players With Chronic Ankle Instability During A Single-leg Jump-landing Task - Amin Farzami; Heydar Sadeghi; Ali Fatahi (Ṭibb-i Tavānbakhshī, 2023)
Background and Aims Although volleyball is a contact sport, there are a high number of injuries in volleyball during training or competitions. Since many jumps are performed during training, it is not surprising that a high number of injuries are caused by jumping and landing. The present study aims to investigate the effect of taping on the feedforward activity of non-dominant leg muscles during single-leg jump-landing in professional volleyball players with chronic ankle instability.Methods In this study, participants were 13 volleyball players with chronic ankle instability who were selected by a purposive sampling method. Electromyographic activity of peroneus longus, anterior tibialis, gastrocnemius, vastus lateralis, gluteus medius, and rectus femoris muscles of the non-dominant leg during a single-leg jump-landing task following a spike shot before and after taping was evaluated. Root mean square was used to calculate muscle activity before and after taping. The data were analyzed using paired t-test. The significance level was set at 0.05.Results The findings showed the significant effect of taping only on maximum feedforward activity (P=0.02) and average feedforward activity (P=0.03) of the peroneus longus muscle. The effect was not statistically significant for other muscles (P>0.05).Conclusion It seems that taping is not useful for improving the feedforward activity of muscles in volleyball players with chronic ankle instability during single-leg jump-landing. Hence, other exercises or methods are recommended for these players during recovery or training.